The Influence of Rapid Tempering on the Mechanical and Microstructural Characteristics of 51CrV4 Steel - Antti Kaijalainen; Oskari Haiko; Saeed Sadeghpour; Vahid Javaheri; Jukka Kömi (Metals, 2024)
The microstructure and mechanical properties of a low-alloy medium carbon steel (Fe-0.5C-0.9Mn-1Cr-0.16V, in wt.%) were investigated after rapid tempering and compared with a conventionally tempered counterpart. The conventional thermal cycle was performed in a laboratory-scale box furnace while rapid heat treatments were carried out using the Gleeble 3800 thermomechanical simulator machine. In the rapid heat treatments, the heating rate was 50 °C/s for austenitizing and 60 °C/s for the tempering process, with a cooling rate of 60 °C/s for both treatments. Austenitization was performed at 900 °C for 3 s and tempering was conducted at 300 °C and 500 °C for 2 s. For conventional routes, the heating rate for both austenitization and tempering was 5 °C/s. Likewise, the austenitization was carried out at 900 °C for 45 min and tempering was carried out at 300 °C and 500 °C for 30 min. The results revealed that rapid tempering resulted in a significantly increased impact toughness compared to conventional tempering, while maintaining a consistent high strength level. The quenched samples showed the highest hardness and tensile strength but obtained the lowest toughness values. The optimum combination of strength and toughness was achieved with the sample rapidly tempered at 300 °C, resulting in a tensile strength of 2050 MPa and impact energy of 14 J for sub-sized CVN samples. These desirable mechanical properties were achieved throughout the tempered martensitic microstructure with a minor fraction of pearlitic strings.